2009
DOI: 10.1007/s10660-009-9034-4
|View full text |Cite
|
Sign up to set email alerts
|

ICT solutions and labor productivity: evidence from firm-level data

Abstract: This paper analyses the impacts of information and communication technology (ICT) solutions on labor productivity, i.e. revenue per employee. Based on cross-sectional data on 1955 European firms in 2005 and a linear regression model derived from the microeconomic theory of production, the impacts of six common ICT solutions in electronic commerce (e-commerce) cannot be ignored. According to the linear regression analysis, Internet access, standardized data exchange with the trading partners, enterprise resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 30 publications
0
15
0
8
Order By: Relevance
“…In the same direction, Welker, van der Vaart, and van Donk (2008) outline that ICTs support the digitisation process of a SCM due to virtual nodes which generate multi-level relational network. In this line, the improvement of SMEs' economic performances using ICTs are linked to skills and abilities (Chesbrough and Spohrer 2006;Nurmilaakso 2009; Soto-Acosta, Casado-Lumbreras, and Cabezas-Isla 2010), attitudes and behaviours of human resources (Peña and Villasalero 2010;Pena et al 2015). Vachon and Klassen (2008) also show that the success of collaborative strategies inside the supply chain is strongly affected by the level of involvement of ICTs human resources which are limited and there are high costs involved.…”
Section: Study Of Hypothesesmentioning
confidence: 99%
“…In the same direction, Welker, van der Vaart, and van Donk (2008) outline that ICTs support the digitisation process of a SCM due to virtual nodes which generate multi-level relational network. In this line, the improvement of SMEs' economic performances using ICTs are linked to skills and abilities (Chesbrough and Spohrer 2006;Nurmilaakso 2009; Soto-Acosta, Casado-Lumbreras, and Cabezas-Isla 2010), attitudes and behaviours of human resources (Peña and Villasalero 2010;Pena et al 2015). Vachon and Klassen (2008) also show that the success of collaborative strategies inside the supply chain is strongly affected by the level of involvement of ICTs human resources which are limited and there are high costs involved.…”
Section: Study Of Hypothesesmentioning
confidence: 99%
“…7, No. 19; explains such a positive relationship (Cooper (2003); Nurmilaakso (2009);Mjema et al (2005);and Velcu (2010)). …”
Section: Discussionmentioning
confidence: 99%
“…Empowering employees by giving them timely information boosts productivity, and this can be done by using an integrated technology such as enterprise resource planning system (ERP). Nurmilaakso (2009) stated that one of the reasons behind investing in ICT solutions is to improve labor productivity, where the ERP system has a positive influence on labor productivity.…”
Section: Productivitymentioning
confidence: 99%
“…Such advances have enabled business organizations to implement ICTs technologies in the day to day operation. Employees' dependency on ICTs for their daily operation has proliferated over the past two decades (Nurmilaakso, 2009). Moreover, numerous studies have demonstrated a significant impact of ICTs (i.e.…”
Section: Introductionmentioning
confidence: 99%